Mechanisms of flavonoids in quinoa’s response to flooding stress in grain filling stage - Jiang, Guofei; Wang, Xuqin; Jiang, Qingwen; Bai, Yutao; Zhang, Lingyuan; Zhang, Ping; Liu, Junna; Li, Li; Li, Hanxue; Huang, Liubin; Zhang, Shan; Qin, Peng (Frontiers in Plant Science, 2025)
Quinoa is a new crop with high nutritional value. Flooding stress plays an important role in constraining the growth and development of quinoa during the filling stage, and flavonoids have been shown to have important roles in abiotic plant stress; however, the mechanisms by which flavonoids respond to quinoa flooding stress during the filling stage are not clear. Therefore, we used Dian quinoa-1844 as the material and employed transcriptomics, metabolomics and bioinformatics techniques to study quinoa leaves under flooding stress during the filling stage. The results showed that 433 flavonoid metabolites were detected in the metabolome. Genes related to flavonoids in the transcriptome were significantly enriched in both GO and KEGG. Integrated transcriptomic and metabolomic analyses revealed 18 flavonoid metabolites and 30 genes exhibiting significant alterations under stress treatment. These 30 genes regulate flavonoid accumulation by modulating the activity of enzymes such as F3H, CHI, and CHS, thereby enhancing quinoa’s resistance to flooding stress. Network interaction analysis identified 5 core transcription factors, 2 core structural genes, and 4 key metabolites. These components synergistically regulate flavonoid biosynthesis to alleviate oxidative damage caused by flooding. This study elucidated the roles and mechanisms of flavonoids in quinoa’s response to flooding stress, providing a theoretical basis for selecting and breeding quinoa varieties with high flooding tolerance.